Investigate the Role of Emotional Intelligence and Employee Performance Level in Forming Organizational Culture Case Study: Polymer Accessories Manufacturer - Bakhtabad, Somayeh Sadat Mahmoudzadeh; Taji, Mohammad (International Journal of Psychosocial Rehabilitation, 2020)
— Introduction: Considering the identification of human resources complications in the studied organization, this study originated from the hypothesis of the effect of emotional intelligence on the formation of organizational culture. According to this fact that the formation of culture of any society roots in the individual’s behaviors of its members, organizational culture is no exception to this rule. Undoubtedly, one of the important factors influencing individual behavior is the level of staff’s emotional intelligence; thus, this study addresses the relationship between staff’s emotional intelligence level, individuals’ performance and organizational culture. Methods: This research has been conducted analytically, survey and statistically. The required tool for collecting data on the level of emotional intelligence and cultural attitude is questionnaire that is completed in a survey form. Two valid questionnaires of EQ evaluation were used for comparative evaluation which were invented by Baron and Syberia shering (Goleman) and their validation and reliability were proved by the previous studies. Indigenous questionnaires of Goleman and Baron contain 33 and 90 questions respectively and they were distributed and completed for a 164-person sample based on the statistical population of more than 280 people. The data on staff’s performance level was distributed and completed by using a checklist design of performance evaluation with %95.2 reliability with method of 360 degrees by managers, customers, peer pressure and subordinate pressure. Cultural attitude data was also collected using Hofstede’s cultural attitude questionnaire whose reliability has been confirmed by Pasha (2011) by Cronbach’s alpha coefficient of %79. The data was used in SPPS software for statistical analysis. Statistical analysis using Cronbach’s alpha coefficient to measure reliability, Kolmogorov- Smirnov test to measure data normality and Kruskal-Wallis test to evaluate the relationship between variables were done. Findings: Both Goleman and Baron emotional intelligence confirm a significant relationship between risk- avoidance/risk-taking as well as power distance. None of Goleman and Baron emotional intelligence has dramatic relation to collectivism-individualism dimension of Hofstede’s cultural attitude. However, there is a significant relation between femininity-masculinity dimension and Goleman’s emotional intelligence and there is no dramatic relation between Baron’s emotional intelligence and the mentioned dimension. Staff’s performance shows no significant relation to Hofstede’s cultural attitude dimensions in any of general and specialized performance dimensions. Conclusion: Although the level of staff’s performance is not significantly related to cultural attitude, due to the impact of Goleman’s emotional intelligence dimensions on individual characteristics and the level of staff’s performance and organizational culture, the indirect and implicit effect of organizational culture and the level of staff’s performance may be significant. Instructional programs and staff’s individual development leading to the improvement of emotional intelligence dimensions can also be effective in promoting organizational culture.